Solid organ transplantation after hematopoietic stem cell transplantation in childhood: A multicentric retrospective survey. Issue 6 (25th January 2019) - Faraci, Maura; Bertaina, Alice; Dalissier, Arnaud; Ifversen, Marianne; Schulz, Ansgar; Gennery, Andrew; Burkhardt, Birgit; Badell Serra, Isabel; Diaz‐de‐Heredia, Cristina; Lanino, Edoardo; Lankester, Arjan C.; Gruhn, Bernd; et al.
Abstract : We report data obtained from a retrospective multicenter pediatric survey on behalf of the European Society for Blood and Marrow Transplantation (EBMT). Information on solid organ transplantation (SOT) performed in pediatric recipients of either autologous or allogeneic hematopoietic stem cell transplantation (HSCT) between 1984 and 2016 was collected in 20 pediatric EBMT Centers (25.6%). Overall, we evaluated data on 44 SOTs following HSCT including 20 liver (LTx), 12 lung (LuTx), 6 heart (HTx), and 6 kidney (KTx) transplantations. The indication for SOT was organ failure related to intractable graft‐vs‐host disease in 16 children (36.3%), acute or chronic HSCT‐related toxicity in 18 (40.9%), and organ dysfunction related to the underlying disease in 10 (22.8%). The median follow‐up was 10.9 years (95% confidence interval: 1.7‐29.5). The overall survival rate at 1 and 5 years after SOT was 85.7% and 80.4%, respectively: it was 74% and 63.2% after LTx, 83.2% after HTx, and 100% equally after LuTx and KTx. This multicenter survey confirms that SOT represents a promising option in children with severe organ failure occurring after HSCT. Additional studies are needed to further establish the effectiveness of SOT after HSCT and to better understand the mechanism underlying this encouraging success. Abstract : The authors present results of a European Society for Blood and Marrow Transplantation survey about solid organ transplantation performed in children who underwent hematopoietic stem cell transplantation.